The Effect of Accounting Code of Ethics on Business Decisions: A Case Study on Multinational Companies - Nasution, Dito Aditia Darma; Maisyarah, Renny; Chairunisa, Tengku Sheila; Safrianto, Reza; Zebua, Totona Berkat Elsuran; Darwin, Darwin; Ujung, Jhonny Tumpal Parulian; Gulo, Yurniwati (PT Inovasi Pratama Internasional, 2024)
The objective of this study is to examine the impact of the accounting code of ethics on the business decisions made by multinational companies. The accounting code of ethics provides a framework for professional conduct, with the objective of influencing the integrity of business decision-making, particularly in the context of accounting and financial reporting. This research employs a case study approach, focusing on multinational companies that have a robust and internationally recognised accounting system. Through the analysis of qualitative and quantitative data, this study has identified that the implementation of the accounting code of ethics plays a significant role in maintaining transparency, accountability and preventing unethical practices in the business decision-making process.